Immediate Response to Artificial Burning and Cutting in Young Trees of Beech (Fagus sylvatica L.) and Oak (Quercus robur L.) : survival, resprouting ability and tree vigour - Birkedahl, Maria (SLU/Southern Swedish Forest Research Centre, 2004)
Young trees of European beech (Fagus sylvatica L.) and pedunculate oak (Quercus robur L.) were burned with a propane-flamer or cut with a hand-saw with the intention to study their response, in terms of survival, ability to resprout and tree vigour during the first vegetation season after disturbance. An early burning/cutting was performed in May and a late one in July, to see if the response was different because of the time of the year. New sprouts were counted and measured twice on the early treated trees and once on those treated late. The vigour of the trees was determined through comparing the leaf-colour of the trees to a colour-scale. In such an early stage the survival and vigour of the cut trees was hard to determine, because they may need more than one season to start resprouting. The survival of the burned beech and oak trees did not differ much during the first season, but larger trees survived to a much higher extent than thin ones. The ability to make new sprouts as well as the tree-vigour was better for the oaks than for the beeches during the first season.